Silly - Leonard, Marcia.; Watson, Wendy (Bantam Books, 1988)
Illustrates why it is fun to act silly sometimes and where and when such behavior is inappropriate.
"A Bantam little rooster book."
Illustrates why it is fun to act silly sometimes and where and when such behavior is inappropriate.
Keywords: Behavior.; Children / Conduct of life.; Frivolity / Juvenile literature.; Joy / Juvenile literature.